As experiências pedagógicas da implementação da política de educação em tempo integral nas escolas de campo na amazônia paraense. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
The implementation of the More Education Program in rural schools in Brazil has been a challenge for the Brazilian full-time education policy, a challenge that pass trough the context of pedagogical practice, reflected in the pedagogical organization, in the space-time relation, in the conection of activities between shifts, among other aspects. In this way, this research chose as general objective, the understanding about the pedagogical experiences coming from the implementation of the Program in the schools of the countryside, and had the following specific objectives: to analyze the connection between the pedagogic activities of the school shift and the proposals in the extended shift ; to understand the space-time relationship in the organization of pedagogical activities in the daily life of the school; to analyze the relationship between the expansion of the school day and the academic performance of the students. Regarding the locus of the research, we selected five schools from the countryside of the city of Santarém, State of Pará. As for the subjects of the research, five groups of individuals were interviewed (Teachers, Monitors, Parents, Directors, More Education Coordinator).We assume for the development of this study, the qualitative approach supported in the documentary and field research anchored in the technique of content analysis of Bardin. Considering the questions we propose to analyze, the research revealed the fragility in the articulation of the activities of school time and extended time, by factors related to teachers' resistance to the work of the monitors, lack of elucidation and understanding about the proposal of More Education, lack of qualification and proper preparation of schools to receive the Program. In observance of the space - time relationship, in the schools studied, we highlight improvisation as a factor that characterizes the organization of spaces and times, in the scope of conciliating the activities of More Education to the spaces and times inside the schools. In terms of advances, we pointed out that after the implementation of the Program in schools, the subjects surveyed indicated that the participating students improved their school performance, the interest and interpersonal relationships. We also identify the meaning of school support to the activities carried out by the monitors, strengthening, in this sense, the charitable nature of the proposal.
Keywords: Política educacional; Educação em tempo integral; Educação do Campo; Programa Mais Educação; CNPQ::CIÊNCIAS HUMANAS; EDUCAÇÃO